Assessing the impact of phronetic leadership behaviors on management innovation and learning dynamic capability - Malik Umer Ayub; Abdul Rashid Kausar; Shajara Ul-Durar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Management innovation is the process of introducing new management practices, processes, and structures. It is considered essential to improve organizational performance and develop competitive advantage. While drawing on the rational perspective this research focuses on management innovation at firm level to empirically examine the impact of various phronetic leadership behaviors on learning dynamic capability of organization. The top management due to its prominent position in the organizations possess the ability to significantly affect management innovation to promote organizations' capability for success. Data was collected from 215 executives working at the positions of CEO, top management teams, and senior managers of 400 manufacturing firms. Initially, the use of confirmatory factor analysis (CFA) through AMOS assessed scales validity in the current context of research. Then the use of structural equation modeling (SEM) helped to test the relationships among hypothesized variables. Results found significant positive impact of CEO and top management team reflexivity and senior managers diagnostic and implementation capability as part of phronetic leadership behaviors on management innovation. Also, management innovation mediated the relationship between phronetic leadership behaviors and learning dynamic capability of organization. This study contributes both theoretically and empirically by developing and testing the framework involving management innovation with respect to its antecedents and consequences in the context of manufacturing sector of Pakistan.
Keywords: 330; Management innovation; phronetic leadership behaviors; CEO and top management team reflexivity; senior managers diagnostic and implementation capability; learning dynamic capability